2013
DOI: 10.1007/s00737-013-0379-2
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal depressive symptoms and abnormalities of glucose tolerance during pregnancy among Hispanic women

Abstract: The aim of this study is to prospectively examine the association between maternal depressive symptoms in early pregnancy and risk of abnormal glucose tolerance (AGT) and impaired glucose tolerance (IGT) in mid-pregnancy. We evaluated this association among 934 participants in Proyecto Buena Salud, a prospective cohort study of Hispanic (predominantly Puerto Rican) women in Western Massachusetts. Depressive symptoms were assessed in early pregnancy using the 10-item Edinburgh Postnatal Depression Scale. Scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Overall, 48 publications were included in this review (Figure 1, Table 1, Table 2, Table 3, Supplementary Table 1). Of these, 30 described prospective observational studies[20,21,23,24,26,27,29-31,34,35,37,38,41,43-45,47-49,51,54,57,58,60-62,65-67], 15 described retrospective observational studies[22,25,28,32,39,40,42,46,50,53,55,56,59,63,64], and three described randomized controlled trials (RCTs)[33,36,52], two of which reported only baseline data[36,52]. Two publications described the same study, but reported different subgroup analyses[23,29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 48 publications were included in this review (Figure 1, Table 1, Table 2, Table 3, Supplementary Table 1). Of these, 30 described prospective observational studies[20,21,23,24,26,27,29-31,34,35,37,38,41,43-45,47-49,51,54,57,58,60-62,65-67], 15 described retrospective observational studies[22,25,28,32,39,40,42,46,50,53,55,56,59,63,64], and three described randomized controlled trials (RCTs)[33,36,52], two of which reported only baseline data[36,52]. Two publications described the same study, but reported different subgroup analyses[23,29].…”
Section: Resultsmentioning
confidence: 99%
“…There were 22 studies that measured depression only during pregnancy[22,24,26,30,31,36,37,40,41,43,45,51,53-55,57-59,61,64,66,67]. Conversely, 11 studies focussed on postpartum depression, most commonly measured within the first 3 mo[20,21,23,25,27,29,33,47,52,62,63].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Racial disparities may also play a role, with Hispanic populations less likely than Caucasian populations to display this association 79,81 . Conversely, the available studies examining GDM as a risk factor for postpartum depression have either not found an association 75,82 or else found that when a relationship is present, it is explained by adjustment for medical comorbidities 83,84 .…”
Section: Inflammatory Mediators: Parallels Between Gestational Diabetmentioning
confidence: 99%
“…GDM risk factors include overweight/obesity 4 and sociodemographic factors such as minority race and low SES. 5 Psychosocial factors, such as stress 6 and prenatal depression, 7,8 may also contribute to GDM.…”
Section: Introductionmentioning
confidence: 99%